IDEAS FOR EXTENDING LIFE IN ANCIENT CULTURES (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article offers a historical and philosophical analysis of the formation and development of ideas about life extension in ancient cultures. The study examines concepts aimed at prolonging lifespan, shaping a healthy lifestyle, and slowing aging in the civilizations of the Ancient East, Greece, and Rome, as well as in Chinese and Indian cultures. It demonstrates that in ancient medicine, religious beliefs, mythological worldviews, and philosophical doctrines, human longevity was interpreted in relation to the laws of nature, moral purity, spiritual balance, and healthy living. The paper further substantiates that ideas about life extension сформulated in antiquity served as an important theoretical foundation for the development of modern gerontology and medical science.
Keywords: ancient culture, life extension, longevity, healthy lifestyle, philosophical views, religious beliefs, mythology, gerontology, medicine, spiritual balance.